Eligibility Recipients Determination of El-Nino Direct Cash Aid Using C4.5 Algorithm - Dini Elldrica Putri; Dwi Marisa Efendi; Siti Aminah (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2024)
The El Nino phenomenon, which causes increased temperatures and prolonged drought, is predicted to continue to hit Indonesia until the end of 2023. The significant impacts of El Nino include reducing the productivity of agricultural products, including food crops such as rice. This condition will certainly greatly affect the stability of domestic food prices. A total of 420 people from Bernah Village, Kota Alam Subdistrict received it. In the selection process for BLT El Nino recipients in Bernah Village, problems often occur such as problems in identifying aid recipients. This creates a society where aid recipients are still relatively well-off. By applying the C4.5 Algorithm, the C4.5 Calculation can determine feasibility thereby increasing efficiency in determining El Nino Direct Cash Assistance receipts. Calculations using Microsoft Excel 2010 revealed that there were 252 eligible recipients while 168 were not eligible. And from the calculation results using Rapid Miner 10.1. It is known that the accuracy rate is 100.00% with a total of 420 people receiving aid data.